Nanotechnological strategies for systemic microbial infections treatment: A review - dos Santos Ramos, Matheus Aparecido [UNESP]; dos Santos, Karen Cristina [UNESP]; da Silva, Patrícia Bento; de Toledo, Luciani Gaspar [UNESP]; Marena, Gabriel Davi [UNESP]; Rodero, Camila Fernanda [UNESP]; de Camargo, Bruna Almeida Furquim [UNESP]; Fortunato, Giovanna Capaldi [UNESP]; Bauab, Taís Maria [UNESP]; Chorilli, Marlus [UNESP] (Elsevier, 2020)
Systemic infections is one of the major causes of mortality worldwide, and a shortage of drug approaches applied for the rapid and necessary treatment contribute to increase the levels of death in affected patients. Several drug delivery systems based in nanotechnology such as metallic nanoparticles, liposomes, nanoemulsion, microemulsion, polymeric nanoparticles, solid lipid nanoparticles, dendrimers, hydrogels and liquid crystals can contribute in the biological performance of active substances for the treatment of microbial diseases triggered by fungi, bacteria, virus and parasites. In the presentation of these statements, this review article present and demonstrate the effectiveness of these drug delivery systems for the treatment of systemic diseases caused by several microorganisms, through a review of studies on scientific literature worldwide that contributes to better information for the most diverse professionals from the areas of health sciences. The studies demonstrated that the drug delivery systems described can contribute to the therapeutic scenario of these diseases, being classified as safe, active platforms and with therapeutic versatility.
Keywords: Drug delivery systems; Nanotechnology; Sepsis treatment; Systemic infections